2003
DOI: 10.1097/01.asn.0000078803.53165.c9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podocyte-Associated Molecules in Acquired Human Kidney Diseases

Abstract: Abstract. Proteinuria is a poorly understood feature of many acquired renal diseases. Recent studies concerning congenital nephrotic syndromes and findings in genetically modified mice have demonstrated that podocyte molecules make a pivotal contribution to the maintenance of the selective filtration barrier of the normal glomerulus. However, it is unclear what role podocyte molecules play in proteinuria of acquired renal diseases. This study investigated the mRNA and protein expression of several podocyte-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
200
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(232 citation statements)
references
References 50 publications
12
200
1
9
Order By: Relevance
“…Mutations in such genes often do not cause early embryonic lethality but rather manifest disease at the time when the function of these genes becomes critical for a specific tissue and subsequently for organismal survival (D'Agati 2008). In acquired disease like diabetes or hypertension, the vulnerability of a specific organ to the systemic disease is defined by the expression of tissue-specific genes (Doublier et al 2003;Koop et al 2003;Woroniecka et al 2011). Defining cell-lineage-specific transcripts therefore has immediate clinical implications for such cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in such genes often do not cause early embryonic lethality but rather manifest disease at the time when the function of these genes becomes critical for a specific tissue and subsequently for organismal survival (D'Agati 2008). In acquired disease like diabetes or hypertension, the vulnerability of a specific organ to the systemic disease is defined by the expression of tissue-specific genes (Doublier et al 2003;Koop et al 2003;Woroniecka et al 2011). Defining cell-lineage-specific transcripts therefore has immediate clinical implications for such cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…From an etiological standpoint, FSGS may be associated with a variety of conditions, including viral infections (human immunodeficiency virus [HIV], simian virus 40 [SV40] , parvovirus B19), several drugs (heroin, pamidronate, interferon), adaptive to hyperfiltration (as in hypertension, obesity, and sickle-cell anemia), and genetic disorders (familiar forms), and may be idiopathic (11) . Podocyte injury is the core pathophysiological event of FSGS and some studies have found anomalous expression of podocyte proteins in FSGS (2,10,16) Table and Figure). Studies of these variants demonstrated correlation with distinct clinical characteristics and prognostic and therapeutic implications (4,18) .…”
Section: Introductionmentioning
confidence: 99%
“…These genomic studies lead to the determination of a molecular topology for SD, required for maintaining the homeostasis of podocytespodocytes [21]. Notably, the decreases of SD-related molecules (such as podocin and CD2AP) are observed in many types of CKD, regardless of the primary etiology [1,19].…”
mentioning
confidence: 99%